The problem of translating certain old Serbian terms in the light of the Dušan’s Code [14th-century] - Majzer, Mateusz (Mundus Slavicus I, 2025)
The article will be devoted to presenting some terms appearing in the Dušan’s Code, which do not have an equivalent in Polish and therefore form a challenge for a potential translator of the Old Serbian text. These include, among others, concepts that acquire new, technical meanings within the text being developed, as well as names of social states and roles that do not exist today or are unknown to the Polish language. The aim of the paper is therefore to familiarize the reader with selected issues, present an analysis of the meanings of individual words and propose optimal [in the researcher’s opinion translation solutions, considering the specific, legal, and therefore specialist nature of the translated text.